Pictures and drawings and their communicative impact in the textbook Reading book for the first stage (model) (Journal of the College of Basic Education, 2022)
The textbook is one of the important tributaries and assistance to the education process and its general goals. It is an important means of communicating structured information about materials, content and teaching methodologies. Many of its elements and design principles are recorded as interactive means of communication for the topics contained in that book. As the subject of pictures and drawings in the textbook needs more attention and study by researchers, of this importance and access to the main paths of the subject of research tagged (images and graphics and their impact in the textbook) identified the problem of research according to the following question: What are the design processes that attract the child's attention in the printed textbook? Through this research we seek to find solutions to this question, and through four chapters, the first chapter included the problem of research, and then the importance of research and identified by the following points: Contribute to the development of performance processes for the designs of images and drawings. Contributes to clarifying the intellectual and practical aspects of the communication process. The research objective is as follows: - Identify the design processes of the methods of designing and displaying images and drawings in the textbook. The researcher also identified three dimensions: Objective Limit: Studying (images and drawings and their communicative effect in the textbook). Spatial Limit: Books issued by the General Directorate of Iraqi Curricula. - Time Limit: Books issued in 2017. The researcher knew the terms related to the subject of the research, which are considered as reliable foundations in the literature of specialization and there were the following terms: image. school book . The second chapter included the theoretical framework, the concept of images and drawings in the design, the child's perception of the images, drawings and colors in the design of the reading book, the communicative and functional role of pictures and drawings. The concept and importance of textbooks. The theoretical framework was followed by a set of indicators that summarize the outcome of this framework. The third chapter dealt with the research procedures that included the research community which consists of the designs of pictures and drawings for the reading material for the first grade. The models were chosen according to the descriptive method in the analysis to reach the results that achieve the research objective. Then analyze some of the selected models for the first grade reading book. The fourth chapter included the results, which the researcher mentions some of them: - Attract attention can be achieved through the shape, color, overlapping, overlapping and intersecting processes. - Diversity in showing sizes, shapes and colors gives a hint of movement and excitement. The conclusions are: - The advantages of using images and drawings that have a significant impact in delivering the idea to the recipient (student). - Free some models of images and rely on the fees greatly. Then came the recommendations, which include: - The use of the design bases and the study of spatial formal relationships that strengthen the organization of the topographical vocabulary because of their role in attracting the attention of the recipient and the characteristics of expressive contained in the elements Karafikip. The proposals include: - Study the effect of color in educational publications. Then the list of sources on which the search was based.